Papagahan: a culturally grounded environmental communication model for strengthening eco-social literacy - Putri, Liza Diniarizky; Mardiana, Siska; Annisarizki,; Hasanah, Budi; Mutoria, Hanifah; Dhiyaulhaq, Muhammad Najmi (Frontiers in Communication, 2026)
The accelerating global wicked problems—ranging from climate change and environmental degradation to digital disruption and cultural erosion—pose serious obstacles to the achievement of the UN Sustainable Development Goals (SDGs). While policy and technology often dominate the discourse, the communicative dimension of these challenges remains underexplored. This article examines Papagahan, a traditional oral and participatory practice of the Baduy community in Indonesia, as a community-based communicative framework that addresses eco-social literacy gaps among youth. Through Participatory Action Research (PAR), ethnography, and participatory observation, five Papagahan sessions were implemented to transform local knowledge into collective planning actions, producing tangible outputs such as biopore systems, waste signage, and local technology-use regulations. Findings demonstrate that Papagahan revitalizes intergenerational communication, strengthens trust and social cohesion, and equips youth as co-planners of sustainability solutions. Beyond its local context, Papagahan illustrates how human communication rooted in cultural wisdom can function as a decolonized communicative praxis for addressing global wicked problems and advancing SDGs 4, 11, 13, 15, and 16. This study contributes to theoretical debates on communication for development and social change by situating local communicative systems as critical enablers of sustainable and equitable futures. Hence, this study offering an alternative lens that challenges dominant paradigms in environmental communication and participatory development.